Triterpenes and sterol from Hoya mindorensis - Ebajo, Virgilio D. (Animo Repository, 2014)
Chemical investigation of the dichloromethane extract of the air-dried roots of Hoya mindorensis Schlechter afforded lupenone (1) and lupeol (2). The leaves yielded 2, squalene (3) and β-sitosterol (4), while the stems afforded betulin (5). The structures of 1-5 were identified by comparison of their 1H and/or 13C NMR data with those reported in literature.